MMP23B expression and protein levels in blood and urine are associated with bladder cancer. (20th July 2018) - Allione, Alessandra; Pardini, Barbara; Viberti, Clara; Giribaldi, Giuliana; Turini, Stefano; Di Gaetano, Cornelia; Guarrera, Simonetta; Cordero, Francesca; Oderda, Marco; Allasia, Marco; Gontero, Paolo; Sacerdote, Carlotta; et al.
Abstract : We investigated the role of MMP23B as a biomarker for urothelial bladder cancer (UBC) and found it downregulated in peripheral blood mononuclear cells from UBC. Levels of urinary MMP23B protein and five miRNAs targeting the gene increased in cases. Present outcomes indicate a potential MMP23B role as non-invasive UBC biomarker. Abstract: Urothelial bladder cancer (UBC) represents a public health problem because of its high incidence/relapse rates. At present, there are no suitable biomarkers for early diagnosis or relapse/progression prognosis. To improve diagnostic accuracy and overcome the disadvantages of current diagnostic strategies, the detection of UBC biomarkers in easily accessible biofluids, such as urine, represents a promising approach compared with painful biopsies. We investigated the levels of MMP23 genes (microarray and qPCR) and protein (western blot and enzyme-linked immunosorbent assay) in a set of samples (blood, plasma and urine) from patients with UBC and controls as biomarkers for this cancer. MMP23B and its pseudogene MMP23A resulted downregulated in blood cells from UBC compared with controls (66 cases, 70 controls; adjusted P -value = 0.02 and 0.03, respectively). In contrast, MMP23B protein levels in plasma (53 UBC, 49 controls) and urine (59 UBC, 57 controls) increased in cases, being statistically significant in urine. MMP23B dosage observed in urine samples was related to both tumor risk classification and grading. As the lack of correlation between mRNA and protein levels could be due to a posttranscriptional regulation mediated by microRNAs (miRNAs), we investigated the expression of urinary miRNAs targeting MMP23B . Five miRNAs resulted differentially expressed between cases and controls. We reported the first evidence of MMP23B secretion in plasma and urine, suggesting a role of this poorly characterized metalloproteinase in UBC as a potential non-invasive biomarker for this cancer. Further analyses are needed to elucidate the mechanism of regulation of MMP23B expression by miRNAs.